A team-based translational journal club: Understanding the translational research highway. Issue 6 (4th December 2019) - Feghali-Bostwick, Carol; Harvey, Jillian; Hasseler, Carissa; Lee-Chavarria, Diana; Halushka, Perry
Abstract: The mission of the National Center for Advancing Translational Science (NCATS) is to catalyze the generation of innovative methods and technologies that will enhance the development, testing, and implementation of diagnostics and therapeutics across a wide range of human diseases and conditions. 1 NCATS funded a predoctoral TL1 training grant at our institution. We developed a novel team-based Translational Journal Club utilizing three-member teams to find a basic science paper and two clinical study papers that covered a single therapeutic, either a pivotal study or a dissemination and implementation study; one member of the team presented a paper on the above topics in successive weeks. In addition, the trainees attended lectures on: how to design a pivotal clinical trial, dissemination and implementation, and drug development from a basic science discovery through its approval. From these presentations, the trainees appreciated the T0 to T3/4 continuum and its challenges. They also attended sessions on how to present scientific concepts, making them better communicators. The trainees found the Translational Journal club to be very rewarding, illuminating, and providing a much better understanding of the translational research processes required to develop new therapies.